ANALISIS KESALAHAN BERBAHASA PADA BIDANG SINTAKSIS DALAM KARANGAN DESKRIPSI SISWA KELAS X SMK PELITA BANGSA BOYOLALI - Wardani, Kusuma, Dra. Atiqa Sabardila, M. Hum (2016)
Kusuma Wardani/A310120099. ANALISIS KESALAHAN BERBAHASA PADA BIDANG SINTAKSIS DALAM MENULIS KARANGAN DESKRIPSI SISWA KELAS X SMK PELITA BANGSA BOYOLALI. Skripsi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Juni, 2016. This study has two objectives: (1) describe and explain the mistakes in the language in the field of syntax in the essay writing descriptions of class X SMK Pelita Bangsa Boyolali, and (2) describe and explain the analysis of the mistakes in the language in the field of syntax in the essay writing descriptions graders X SMK Pelita Bangsa Boyolali. This research is a descriptive qualitative research. Sources of data in this study is the description of the bouquet of class X SMK Pelita Bangsa Boyolali. The data is a form of language errors in the essay description. Data collection techniques in this research is observation, interview and documentation study, miscellaneous motode data provision by using methods refer to and acted upon using the log. Data were analyzed using a unified method and agih. Results of research on error analysis in the field of syntax in the essay writing descriptions of class X SMK Pelita Bangsa Boyolali can be divided into nine aspects. (1) Sentence structure not standard, (2) The sentence is ambiguous. (3) The sentence is unclear, (4) diction is not appropriate in forming sentences, (5) Contamination sentence, (6) Coherence, (7) The use of the word redundant, (8) The word uptake used in a sentence, and (9) Logic sentence. Keywords: bouquet, syntax, linguistic fault, error solutions.